Proposição da implementação do city manager em municípios brasileiros - Mischiatti, João Augusto Wendt (2017)
Currently, in the Brazilian reality, many municipalities face difficulties to implement an efficient management and to reduce the corruption rates. This comprovation motivated the search for a new model of government and management to be analyzed. Therefore, the main objective of this study is to propose the use of the city manager in the brazilian´s cities, whose functions will be adapted to the context and reality of the country. Initially, a bibliographic and documentary analysis was carried out to support the development of the study proposal. Thus, international articles and legislation relating to the city manager were analyzed. As for its purpose, it is an applied research and an exploratory and explanatory research as its general objectives. The approach used for this study was qualitative. The qualitative step was operationalized through a bibliometric and documentary analysis. In order to complete the bibliometric study, journals were searched in the Scopus, Web of Science and SciELO databases, using the term "City Manager" as a key word. In the same way, searches were made on legislation and contracts related to the position of City Manager. Subsequent to the collection of information, the results obtained were interpreted using the technique of content analysis. Among the results presented, we highlight the suggestion of a Law proposed regarding the implementation of the city manager in Brazilian prefectures. This proposal was elaborated after the analysis of several American legislation and scientific articles illustrating the main common and important points on the subject. It should be noted that in order to propose this legislation, it was necessary to adapt the position to the requirements and characteristics established in Brazilian legislation.